Ant-1, an active transposon from the fungus Aspergillus niger - Glayzer, D.; Roberts, I.; Archer, D.; Oliver, Richard (1995)
A transposable element has been isolated from the industrially important fungus Aspergillus niger (strain N402). The element was identified as an insertion sequence within the coding region of the nitrate reductase gene. It had inserted at a TA site and appeared to have duplicated the target site upon insertion. The isolated element was found to be 4798 by in length and contained 37-bp inverted, imperfect, terminal repeats (ITRs). The sequence of the central region of the element revealed an open reading frame (designated ORF1) which showed similarity, at the amino acid level, to the transposase of the Tc1/mariner class of DNA transposons. Another sequence within the central region of the element showed similarity to the 3 coding and downstream untranslated region of the amyA gene of A. niger. Sequence homology and structural features indicate that this element, which has been named Ant1 (A. niger transposon 1), is related to the Tc1/mariner group of DNA transposons. Ant1 is apparently present as a single copy in strain N402 of A. niger.